13. MUCINOUS MICROPAPILLARY CARCINOMA OF THE BREAST. (February 2015) - Forsyth, A.; Egerton, M.
Abstract : Introduction: Mucinous micropapillary carcinoma of the breast (MUMPC), also described as 'pure mucinous carcinoma with micropapillary pattern', is a newly recognised entity with histological features of both mucinous carcinoma and invasive micropapillary carcinoma. It has been observed to behave in a way intermediate between these subtypes. Case summary: A 38-year-old woman was found to have a right-sided 8 cm breast lump and axillary lymphadenopathy. Mammography showed a large area of abnormality and microcalcifications. Core biopsies of the breast and axilla showed an infiltrating carcinoma with mucinous and micropapillary differentiation. It had a Ki67 proliferation index in the order of 50% and p53 labelling. It was positive for ER and negative for PR and HER2. High grade comedo-type DCIS was present. The patient underwent neoadjuvant chemotherapy. A mastectomy showed a 12 cm MUMPC with 3 of 6 nodes positive. Histological findings of reduced cellularity and a reduction in the Ki67 index indicated a good response to chemotherapy. Post-operatively, she had further chemotherapy followed by radiotherapy and tamoxifen. Discussion: MUMPC is associated with higher rates of lymph node metastasis and lymphovascular invasion than pure mucinous carcinoma and (in some case series) a younger age. The diagnosis is based on a number of features, the most defining being micropapillary formations in the presence of extensive extracellular mucin. In addition, the pathologist should look for: psammomatous calcifications; nuclear pleomorphism; 'hobnail' cells; high Ki-67 labelling and p53 expression. High-grade micropapillary DCIS and HER2 positivity are suggestive. MUC1/EMA staining is not reliable in distinguishing MUMPCs from pure mucinous carcinoma. Conclusion: MUMPCs behave more aggressively than pure mucinous carcinomas. It is therefore important to distinguish them histologically. Further studies will be important in further delineating their characteristics and behaviour.